Lithium-treated nickel-containing metal material and preparation method thereof

Through the lithiation treatment technology, the ion-dipole interaction between lithium ions and hydrogen molecules is used to improve the hydrogen storage capacity and hydrogen absorption/discharge rate of nickel-containing metal organic frame materials, and solve the problems of small hydrogen storage capacity and poor hydrogen absorption/discharge performance of existing MOFs materials.

CN119819270APending Publication Date: 2025-04-15NINGXIA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510052872.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing metal-organic frame materials (MOFs) have small hydrogen storage capacity under mild conditions and poor hydrogen absorption/discharging kinetics.

Method used

By reacting nickel-containing MOFs with a highly reactive lithium ion-containing precursor solution, a lithiated nickel-containing metal organic framework material is formed, and the adsorption of hydrogen molecules is enhanced by ion-dipole interaction between lithium ions and hydrogen molecules.

Benefits of technology

The hydrogen storage capacity and hydrogen absorption/discharge rate of nickel-containing metal organic frame materials are significantly improved, with a maximum hydrogen absorption of up to 4.5 wt.%, and the high specific area and high porosity of the material are maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819270A_ABST
    Figure CN119819270A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of hydrogen storage material preparation, and particularly relates to a lithiated nickel-containing metal material and a preparation method thereof, and lithium ions are introduced into an organic ligand fragment of a nickel-containing metal organic framework. The adsorption of hydrogen molecules is realized by utilizing the ion-dipole interaction between the lithium ion sites and the hydrogen molecules, so that the hydrogen storage performance of the nickel-containing metal organic framework material is improved. The preparation method of the material is simple in process, low in energy consumption and cost and suitable for industrialization; the lithiated nickel-containing metal frame material can obviously improve the hydrogen storage capacity and also can improve the hydrogen absorption rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogen storage material preparation, and in particular relates to a lithium-treated nickel-containing metal material and a preparation method thereof. Background Art

[0002] As an efficient, clean and renewable energy, hydrogen energy has attracted much attention in recent years. Its development and utilization include three key links: hydrogen preparation, storage and transportation, and application. In the entire chain, safe and efficient storage and transportation are crucial. Current research mainly focuses on hydrogen storage materials, covering areas such as activated carbon adsorption hydrogen storage and metal hydride hydrogen storage.

[0003] Metal-organic frameworks (MOFs) are a special type of coordination polymer with a three-dimensional pore structure. It uses metal ions as connection points and organic ligands as support to form a porous material with spatial 3D extension. MOFs have many advantages, such as high porosity, low density, large specific surface area, regular pores, adjustable pore size, and diverse and tailorable topological structures, so they have become a research hotspot in the field of hydrogen storage. Although the porous structure and internal unsaturated metal sites of MOFs are conducive to the hydrogen absorption process, MOFs porous materials have the problems of small hydrogen storage capacity under mild conditions and poor hydrogen absorption / desorption kinetics. Therefore, improving the hydrogen storage capacity of MOFs and improving their hydrogen absorption / desorption kinetics have become an important direction of current research. Summary of the invention

[0004] The present invention aims to provide a method for preparing a lithiated nickel-containing metal organic framework hydrogen storage material, by reacting nickel-containing MOFs with a precursor solution containing lithium ions with high reactivity to form an organic metal framework material containing lithium ions. The material is based on a nickel-containing metal organic framework material with a high specific area and high porosity, introduces lithium ions into the framework through a lithiation reaction, and utilizes the ion-dipole interaction between lithium ions and hydrogen molecules to enhance the adsorption of hydrogen molecules, thereby improving the hydrogen storage performance of the nickel-containing metal organic framework material, and at the same time, such high charge density alkali metal ions can also increase the hydrogen absorption / desorption rate.

[0005] In order to solve the above technical problems, the present invention adopts a solvothermal method to prepare nickel-containing MOFs, and then lithiates the framework by liquid phase reaction treatment to finally obtain the material. The technical solution of the present invention is as follows:

[0006] In some embodiments of the present application, a lithiation-treated nickel-containing metal material and a preparation method thereof are provided, comprising the following steps:

[0007] (1) First, synthesize nickel-containing metal organic framework materials

[0008] Step 1: N,N-dimethylformamide, ethanol and deionized water are measured in a volume ratio of 10 to 20:1:1, and then terephthalic acid is added with 0.01 to 0.015 times the weight of N,N-dimethylformamide under ultrasonic conditions to fully disperse;

[0009] Step 2: Take 0.008 to 0.012 times the weight of nickel chloride hexahydrate of N,N-dimethylformamide, add it to the mixed solution evenly mixed in a, then add 0.05 to 0.08 times the volume of triethylamine of N,N-dimethylformamide, stir well, let stand for a period of time at room temperature, filter and collect solid precipitate, wash and dry the obtained solid precipitate to obtain nickel-containing MOF;

[0010] (2) Preparing precursor solutions for lithiation or sodiumization

[0011] Step 3: In an anhydrous and oxygen-free operating environment, add small lithium metal particles of about 1.5 mm × 1.5 mm to a mixed solvent consisting of 100-500 times the weight of polycyclic aromatic hydrocarbons and ether organic solvents. The volume ratio of polycyclic aromatic hydrocarbons to ether organic solvents can be 1 to 10:1;

[0012] Step 4: After shaking the prepared solution for about 1.5 hours, the color of the mixed solution turns green, then dark green, and finally black;

[0013] Step 5: adding nickel-containing MOF to the precursor solution at a mass ratio of 1:10 to 100, stirring for reaction, and collecting the solid product by centrifugation after the reaction is completed; washing the obtained product with an organic solvent, and drying at 80° C. to obtain the lithium or sodium-treated nickel-containing metal organic framework material;

[0014] In some embodiments of the present application, the lithium metal includes lithium metal particles or lithium sheets;

[0015] In some embodiments of the present application, the polycyclic aromatic hydrocarbons include one or more of naphthalene, pyrene, acenaphthene, and acenaphthylene;

[0016] In some embodiments of the present application, the ether organic solvent includes one or more of tetrahydrofuran, ethylene glycol dimethyl ether, dioxolane, 1,4-dichlorohexacyclopentane, ethylene chloride, and anisole;

[0017] In some embodiments of the present application, the stirring speed of the reaction in step 5 is 100-1000 rpm, the reaction temperature is 0-150° C., and the reaction time is 60 s-10 h.

[0018] In some embodiments of the present application, the organic solvent used for cleaning the product includes one or more of tetrahydrofuran, ethylene glycol dimethyl ether, dioxolane, 1,4-dichlorohexacyclopentane, ethylene chloride, and anisole.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The preparation method of the present invention is simple, the process is easy to control, the cost is low, and it is suitable for industrial promotion;

[0021] 2. The present invention uses a solution method to lithiate the metal organic framework, and the lithiation process can be controlled by adjusting the reaction conditions such as solution composition, ratio, temperature, etc. to achieve a mild reaction, thereby avoiding the disadvantage of the traditional lithiation reaction that violently causes damage to the material structure;

[0022] 3. The lithiated MOFs material has the morphological characteristics of high specific area and high porosity of MOFs materials. At the same time, the alkali metal ions on the framework play a synergistic role in accelerating the hydrogen absorption / desorption process of MOFs materials, significantly improving the hydrogen storage capacity and hydrogen absorption / desorption rate of the materials. Compared with nickel-containing MOFs materials that have not been modified with alkali metal ions, the maximum hydrogen absorption capacity of the modified MOFs materials can reach 4.5wt.%, and the total amount of hydrogen adsorption has been significantly increased. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Moreover, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:

[0024] Figure 1 A schematic diagram of an infrared spectrum characterization curve of a lithiated MOF material provided in an embodiment of the present invention;

[0025] Figure 2 A schematic diagram of a thermal stability characterization curve of a lithiated MOF material provided in an embodiment of the present invention;

[0026] Figure 3 A schematic diagram of a powder X-ray diffraction characterization curve of a lithiated MOF material provided in an embodiment of the present invention;

[0027] Figure 4 Schematic diagram of SEM photos of lithiated and non-lithiated MOF materials provided in an embodiment of the present invention;

[0028] Figure 5 A schematic diagram of a hydrogen absorption performance test curve of lithiated and non-lithiated MOF materials provided in an embodiment of the present invention;

[0029] Figure 6 Schematic diagram of the hydrogen absorption rate test curve of the lithiated MOF material according to an embodiment of the present invention. DETAILED DESCRIPTION

[0030] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0031] In order to better understand the purpose, structure and function of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings.

[0032] See attached Figure 1-6 As shown, according to some embodiments of the present application, the following preparation steps are performed in sequence:

[0033] (1) Take 15 ml of N,N-dimethylformamide, 1 ml of ethanol and 1 ml of deionized water, then add 210 mg of terephthalic acid under ultrasonic conditions, and continue ultrasonic treatment at room temperature for 15 min;

[0034] (2) 180 mg of nickel chloride hexahydrate was added to the solution in (1), shaken for 2 min, and then 1 ml of triethylamine was added. After sufficient stirring, the mixture was allowed to stand at room temperature for 24 h, and the solid precipitate was collected by filtration. The solid precipitate was washed three times with ethanol and deionized water respectively, and then dried in a vacuum oven at 80 °C for 24 h to obtain a nickel-containing MOF.

[0035] (3) In a glove box, 1 g of small lithium metal particles of about 1.5 mm × 1.5 mm were slowly added in batches to 200 ml of a mixed solvent consisting of pyrene and tetrahydrofuran. The volume ratio of pyrene to tetrahydrofuran was 1:5. After the prepared solution was shaken in the glove box for about 1.5 hours, the color of the mixed solution turned green, then dark green, and finally black;

[0036] (4) Take 150 mg of nickel-containing MOF and 200 ml of the mixed solution prepared in step (3) respectively. Add MOF to the solution in batches and slowly, and continue to stir and react for 1 hour. After the reaction is completed, collect the solid product by centrifugation; wash the obtained product with ether three times, and then place it in a vacuum drying oven at 80°C for 24 hours to finally obtain lithium-treated nickel-containing MOFs;

[0037] Figure 1 The infrared spectra of the original and lithiated MOF materials prepared by the present invention are characterized by curves. The original MOF sample shows characteristic peaks of carboxylic acid at 1657cm-1 and 1578cm-1, indicating the successful preparation of MOF. The chemical structure of the lithiated MOF has no obvious change, indicating that the lithiation does not destroy the chemical structure of MOF.

[0038] Figure 2This is a thermal stability characterization curve of the lithiated MOF material prepared by the present invention. It can be seen from the figure that the lithiated MOF loses weight by about x% within 100°C, which is mainly attributed to the weight loss of water adsorbed by the MOF material within this temperature range. In the subsequent 100-500°C, the lithiated MOF material basically does not lose weight, indicating that its structure can remain stable. When the temperature is greater than 500°C, the lithiated MOF material loses weight rapidly, indicating that it undergoes carbonization and decomposition at high temperatures.

[0039] Figure 3 and 4 XRD and SEM photos of the lithiated MOF material prepared by the present invention. The XRD spectrum shows that the sample still retains ordered crystals after the lithiation treatment, which is consistent with the SEM test results. The SEM test shows that the sample is uniformly rod-shaped as a whole, with a length of about 2-5 microns. The sample surface is relatively smooth and has a large specific surface area, indicating that the lithiation treatment does not destroy the high crystallinity of the MOF material itself, so the structural characteristics of the high specific surface area and high porosity of MOF can be retained. These characteristics are conducive to enhancing the interaction between hydrogen atoms and metal active sites, forming a hydrogen overflow effect, and improving the adsorption performance of hydrogen.

[0040] The obtained material was tested for hydrogen storage performance. Figure 5 As shown, the lithiated MOF absorbs hydrogen stably around 316s at room temperature, with a maximum adsorption amount of 3.4wt.%, which is significantly higher than that of the unlithiated MOF material. Figure 6 The results show that the hydrogen absorption rate of lithiated MOF is 0.303wt.% / s. The improvement of the hydrogen storage performance of lithiated MOF is mainly due to the ion-dipole interaction between lithium ions or sodium ions and hydrogen molecules, which can significantly enhance the adsorption of hydrogen molecules, thereby improving the hydrogen storage performance of nickel-containing metal organic framework materials. At the same time, this type of high charge density alkali metal ions can also increase the hydrogen absorption rate.

[0041] In the description of the present application, it should be understood that the terms "center", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.

[0042] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, unless otherwise specified, "plurality" means two or more.

[0043] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0044] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0045] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A lithium-treated nickel-containing metal material and a method for preparing the same, characterized in that: The following steps are involved: Step 1: Take appropriate amounts of N,N-dimethylformamide, ethanol and deionized water and mix them to obtain a first mixed solution, weigh an appropriate amount of terephthalic acid, and mix the terephthalic acid and the first mixed solution under ultrasonic conditions to obtain a second mixed solution; Step 2: Add an appropriate amount of nickel chloride hexahydrate to the second mixed solution and mix well to obtain a third mixed solution, inject an appropriate amount of triethylamine into the third mixed solution, stir well and let stand, collect the precipitate, and wash the precipitate to obtain a nickel-containing MOF; Step 3) adding lithium metal to a mixed solvent consisting of polycyclic aromatic hydrocarbons and an ether organic solvent in an anhydrous and oxygen-free environment to obtain a fourth mixed solution; Step 4) shaking the fourth mixed solution for 1.5 hours to change the color of the fourth mixed solution to black, thereby obtaining a precursor solution; Step 5) Add the nickel-containing MOF to the precursor solution in a corresponding proportion, stir to react, collect the solid product by centrifugation after the reaction, wash the solid product with an organic solvent, and dry it at 80° C. to obtain a lithiated nickel-containing metal organic framework material.

2. The lithiation-treated nickel-containing metal material and the preparation method thereof according to claim 1, characterized in that: The volume ratio of N,N-dimethylformamide, ethanol and deionized water in step 1 is 10-20:1:1; wherein the weight of terephthalic acid is 0.01-0.015 times the weight of N,N-dimethylformamide.

3. The lithium-treated nickel-containing metal material and the preparation method thereof according to claim 1, characterized in that: The weight of nickel chloride hexahydrate in step 2 is 0.008 to 0.012 times the weight of N,N-dimethylformamide; wherein the content of triethylamine is 0.05 to 0.08 times the volume of N,N-dimethylformamide.

4. The lithiation-treated nickel-containing metal material and the preparation method thereof according to claim 1, characterized in that: The lithium metal in step 3 is lithium metal particles or lithium sheets, wherein the size of the lithium metal is 1.5 mm*1.5 mm.

5. The lithium-treated nickel-containing metal material and the preparation method thereof according to claim 1, characterized in that: In the step 3, the weight of the polycyclic aromatic hydrocarbons and the ether organic solvent in the mixed solvent is 100-500 times the weight of the lithium metal; the volume ratio of the polycyclic aromatic hydrocarbons to the ether organic solvent is 1-10:

1.

6. The lithiated nickel-containing metal material and the preparation method thereof according to claim 5, characterized in that: The polycyclic aromatic hydrocarbons include one or a combination of naphthalene, pyrene, acenaphthene and acenaphthylene.

7. The lithiated nickel-containing metal material and the preparation method thereof according to claim 5, characterized in that: The ether organic solvent includes one or a combination of tetrahydrofuran, ethylene glycol dimethyl ether, dioxolane, 1,4-dichlorohexacyclopentane, ethylene chloride, and anisole.

8. The lithiated nickel-containing metal material and the preparation method thereof according to claim 1, characterized in that: The stirring reaction in step 5 is carried out at a stirring speed of 100 to 1000 rpm, a reaction temperature of 0 to 150° C., and a reaction time of 60 s to 10 h.

9. The lithiated nickel-containing metal material and the preparation method thereof according to claim 1, characterized in that: The organic solvent in step 5 includes one or a combination of tetrahydrofuran, ethylene glycol dimethyl ether, dioxolane, 1,4-dichlorohexacyclopentane, ethylene chloride, and anisole.